2013
DOI: 10.3174/ajnr.a3492
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Differences in the Lenticular Nucleus in Type 2 Diabetes Mellitus Shown by Proton MR Spectroscopy

Abstract: BACKGROUND AND PURPOSE:Previous studies by using proton MR spectroscopy found metabolite abnormalities in the cerebral cortex and white matter of patients with type 2 diabetes mellitus. The present study was undertaken to detect metabolite differences in the lenticular nuclei and thalamus in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Previous studies have shown that decreased NAA is associated with impaired neuronal viability, and correlated significantly with the severity of white‐matter disease . In patients with Type 2 diabetes mellitus (T2DM), the NAA levels have also been repeatedly shown to be altered . In addition, it has been confirmed that regional reductions of cerebral blood flow, as well as ischemia and hypoxia, can be found in both diabetic rodents and patients .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies have shown that decreased NAA is associated with impaired neuronal viability, and correlated significantly with the severity of white‐matter disease . In patients with Type 2 diabetes mellitus (T2DM), the NAA levels have also been repeatedly shown to be altered . In addition, it has been confirmed that regional reductions of cerebral blood flow, as well as ischemia and hypoxia, can be found in both diabetic rodents and patients .…”
Section: Discussionmentioning
confidence: 87%
“…36 In patients with Type 2 diabetes mellitus (T2DM), the NAA levels have also been repeatedly shown to be altered. [37][38][39] In addition, it has been confirmed that regional reductions of cerebral blood flow, as well as ischemia and hypoxia, can be found in both diabetic rodents and patients. 40 These changes could impede the delivery of nutrients and oxygen to the brain, thus affecting cerebral energy metabolism and neuronal function.…”
Section: Metabolic Alterations In the Visual Cortexmentioning
confidence: 84%
See 1 more Smart Citation
“…Both human and animal MRS studies of DM suggest a decrease in the N-acetylaspartate (NAA)/creatine (Cr) ratio in a relatively consistent manner, while there are mixed results for the choline (Cho)/Cr ratio [77]. In a study using a rat model of DM, reductions in the NAA/Cr ratio and the NAA/Cho ratio were observed in diabetic rats, whereas the Cr/Cho rate was not significantly changed [78].…”
Section: Neural Correlates Of Neurocognitive Impairment In T2dm: Evidmentioning
confidence: 99%
“…A study reported that the Cho/Cr ratio was decreased in the frontal and parietal lobes of patients with T2DM [81], while another study observed an increase in the occipital lobe [82]. In the most recent MRS study on T2DM, a decrease in the NAA/Cr ratio and an increase in the Cho/Cr ratio in the lenticular nucleus were noted [77]. The literature suggests an association between NAA and neuronal damage, as well as one between Cho and glial proliferation [83].…”
Section: Neural Correlates Of Neurocognitive Impairment In T2dm: Evidmentioning
confidence: 99%